Small-Scale Business Survival and Inheritance: Evidence from Germany - Dorothea Schäfer; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In this paper we investigate whether small-scale businesses face financial constraints that affect their survival. We develop a model of moral hazard in which financial constraints arise endogenously. The model predicts that higher private assets relax financial constraints and have a positive effect on the firm's probability of survival. We test this proposition using German Socio-Economic Panel (GSOEP) data, which cover the period 19842004. The release from financial constraints is measured by inheritance. The empirical analysis confirms that the entrepreneur has a higher propensity to stay in business when she inherits capital. This effect is particularly strong for entrepreneurs that switch from self-employment into wage employment. These results are consistent with hypothesis that financial frictions have a perceptible impact on bankruptcy among small business firms.
Keywords: G30; J20; L10; 330; Entrepreneurship; survival; financial constraints